Zero Baht Health Care Based on the Buddhist Dhamma Medicine Concept - Klajon, Kaewjaiphet; Angasinha , Asst. Prof. Dr.Chatwarun (Journal of Dhamma for Life, 2023)
Objectives of the research “Zero Baht Health Care Based on the Buddhist Dhamma Medicine Concept” 1) To study zero Baht health care based on the Buddhist Dhamma Medicine concept. 2) To study the implementation due to zero Baht health care based on the Buddhist Dhamma Medicine concept. 3) To analyze the concept and the implementation of zero Baht health care based on the Buddhist Dhamma Medicine. In accordance with the framework of holistic health care, social factors about health and the concept of economics. The researching methodologies, qualitative research, documentary research, in-depth interview. The result of the research, Zero Baht health care based on the Buddhist Dhamma Medicine concept is holistic health care by the integration of several methodologies. Due to the understanding of; the interrelationship of all things, problem solve at the root cause by using the highest saving things, but getting the highest utility in simple way, rapid result, self-sufficiency, the main usage of local resources. These methodologies can be applied for sustainable way of lives. Two components which cause success in solving health problems due to the implementation of The Buddhist Dhamma Medicine concept, 1) Self-sufficiency which emphasizes problem solving at the root cause by using the highest saving things, simple, self-helping and getting the highest utility. This is to decrease defilements, superfluous passion. 2) Sharing which emphasizes gathering good persons to join together, sacrificing, doing good things, helping the societies in accordance with their capabilities. This is the creation of real value, true benefit of mankind.